Parcours de femmes twenty years of women in French - Allison, Maggie; Kershaw, Angela (Modern French identities, 2011)
This collection of essays celebrates twenty years of Women in French, a network of female academics working in the discipline of French Studies and investigates the theme of trajectories in French and Francophone women's lives and writings.